KAJIAN KODE DI BALIK RITUAL PERNIKAHAN ADAT SUNDA DAN PERGESERANNYA DI MASA KINI (STUDI KASUS: PERNIKAHAN DI BANDUNG DAN CIAMIS) - Yunisa Fitri Andriani (Universitas Bunda Mulia, 2020)
All sorts of values that are behind a series of traditional Sundanese wedding traditions rituals provide a good moral message for the bridal couple are also parents and family of the bride and groom. Indigenous traditional Sundanese wedding ceremony with all the rituals contained in it is also one of Indonesia's culture deserves to be preserved. However, over the times, appeared outside the present culture and local cultural shift. Beyond the practical culture began to dominate in terms of marriage, affecting people not to use the tradition-laden of meaning and message.